GUARDIANS OF THE EARTH: CULTURAL DIMENSIONS OF EARTHEN ARCHITECTURE IN LADAKH, INDIA - Sharma, Tara (Memorias del Seminario Iberoamericano de Arquitectura y Construcción con Tierra - SIACOT, 2012)
In the arid mountainous region of Ladakh (northern India), people have developed a unique relation with the austere environment in which they live. This is relected in a range of belief patterns and traditions that inluence their habitats. Each Buddhist village has its own mountain deity (lha), which protects the village from evil and misfortune often seen in natural calamities, including drought and loods. The layout of every village is marked by symbols of protection, as are the houses within the village. Rituals and beliefs associated with the construction of traditional earthen- and stone-masonry houses relect this constant need for maintaining a balance with nature. The selection of sites for construction of houses and, even more so, for monasteries and temples is governed by special consultations with astrologers, most notable being the monks from Tagthog monastery in southwestern Ladakh. From the irst digging of the foundations and the placating of the earth lords, to the laying of the roof and the inal blessing of the house, everything is marked by rituals. To this belief was added the deep knowledge of the traditional village mason and carpenter who knew exactly what kinds of mud, stone and timber were to be used for what purpose. Today as these beliefs gradually erode and modern construction materials replace traditional material, the impact is being felt on settlement patterns and the architecture across the region. The lashloods of 2010, one of the worst in living memory, highlighted the loss of some of this traditional wisdom as newer construction fell prey to the wrath of nature. This paper will highlight some of the indigenous practices and beliefs associated with the earthen architecture of the region, the gradual decline of this traditional knowledge base and its resulting impact on Ladakh today.